ISLAMIC BOARDING SCHOOLS (PESANTREN) AND THE CHALLENGES OF MODERNITY: RESPONSES TO THE ADVANCEMENT OF SCIENCE AND TECHNOLOGY - Muhammad Syukri Pulungan; Kombang Tua Siregar; Burhanuddin Siregar; Aris Munandar (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
This study aims to analyze pesantren’s responses to modernity and to uncover the epistemological and practical dynamics that surround them. Modernity is suspected to erode the authority of classical scholarly traditions and displace cultural values, thereby generating fragmentation within pesantren identity. The method employed in this research is library research with a qualitative approach. Data were collected from academic literature and analyzed descriptively through the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that pesantren’s responses to modernity are diverse. First, some pesantren adopt a resistant stance in order to safeguard the authenticity of classical Islamic scholarship. Second, others take a progressive position by integrating science and technology as instruments of institutional transformation. Third, certain pesantren adopt a moderate orientation through selective integration strategies that seek to maintain a balance between the preservation of tradition and the utilization of technology. This study asserts that modernity should not be viewed merely as a threat but rather as a sphere of epistemological negotiation that enables the emergence of a creative synthesis between Islamic tradition and technological innovationn. Keywords: Pesantren; Modernity; Knowledge; Technology; Islamic Education   Abstrak Penelitian ini bertujuan untuk menganalisis respons pesantren terhadap modernitas dan mengungkapkan dinamika epistemologis serta praksis yang melingkupinya. Modernitas disinyalir berpotensi mengikis otoritas tradisi keilmuan klasik dan menggeser nilai kultural yang menimbulkan fragmentasi identitas pesantren. Metode yang digunakan dalam penelitian ini adalah studi pustaka (library research) dengan pendekatan kualitatif. Data dikumpulkan dari literatur akademik yang kemudian di analisis secara deskriptif kualitatif melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa respons pesantren terhadap modernitas bersifat beragam. Pertama, sebagian pesantren menempuh sikap resistif untuk menjaga otentisitas tradisi keilmuan Islam klasik. Kedua, terdapat pesantren yang bersikap progresif dengan mengintegrasikan ilmu pengetahuan dan teknologi sebagai instrumen transformasi kelembagaan. Ketiga, beberapa pesantren mengambil posisi moderatif melalui strategi integrasi selektif yang berusaha menjaga keseimbangan antara konservasi tradisi dan pemanfaatan teknologi. Studi ini menegaskan bahwa modernitas tidak semestinya diposisikan sebagai ancaman, melainkan sebagai ruang negosiasi epistemologis yang memungkinkan lahirnya sintesis kreatif antara tradisi keislaman dan inovasi teknologi. Kata kunci: Pesantren; Modernitas; Ilmu Pengetahuan; Teknologi; Pendidikan Islam